MENINGKATKAN KEMAMPUAN MENGENAL HURUF MELALUI PERMAINAN PETI HARTA KARUN BERISI HURUF PADA ANAK USIA 4-5 TAHUN - Aryani, Trisa (2014)
Penelitianinidilakukanatasdasarpermasalahan yang munculpadaanak-anakkelompokusia 4-5 tahun di KoberAzkiya, yaitupadaumumnyakemampuandalammengenalhurufmasihrendah, haltersebutkarenakegiatanpembelajaran yang kurangmenarikbagianak, inidisebabkan guru yang kurangmengeksplorepermainandanjugakarenaketerbatasan media pembelajaran. Mengenalhurufsangatpentingbagianaksebagaiawalgunapersiapanjenjangakademikberikutnya. KarenaitupenelitimenggunakankegiatanpermainanPetiHarta Karun BerisiHurufuntukmeningkatkanmengenalhurufkelompokusia 4-5 tahunKoberAzkiya. Adapuntujuanpenelitianiniadalahuntukmengetahuikondisiawaldanakhirkemampuanmengenalhurufdi KoberAzkiyadanuntukmengetahuipenerapanpermainanPetiHarta Karun BerisiHuruf di KoberAzkiya. Metode yang digunakanadalahPenelitianTindakanKelas (PTK) yaitusubjeksebanyak 11 orang anak, yang dalampelaksanaanyaterdiridaritigasiklus, siklus I dansiklus II diberiduatindakansedangkansiklus III diberisatutindakan. Hasilanalisisdanpembahasandituangkansecaradeskritif. Hasilobservasikemampuanmengenalhurufkelompokusia 4-5 tahunpascasiklus I setelahdiberitindakanmelaluipermainanPetiHarta Karun BerisiHurufterbuktimeningkat, yaitu 37% padakategoribaik, 36% padakategoricukupdan 27% padakategorikurang. Hasilobservasipadapascasiklus II meningkatlagimenjadi 55% padakategoribaik, 45% padakategoricukup. Padapascasiklus III semakinmeningkatmenjadi 73% padakategoribaikdan 27% padakategoricukup. Perkembangantersebutdirasacukup jika dibandingkandengansebelumdiberitindakanmelaluipermainanPetiHarta Karun BerisiHuruf. Rekomendasibagi guru diharapkanmampumemvariasimetodedanstrategipembelajaransehinggapembelajarantidakmonoton. Bagipihaksekolahhendaknyadapatmemfasilitasiuntukmendukung proses belajarmengajar. Bagipenelitidiharapkanmencaridanmenemukanmetodedanstrategi yang berbedauntukmeningkatkankemampuanmengenalhurufbagianakusiadni This research was conducted on the basis of problems that arise in children the age groups of 4-5 year in KoberAzkiya, the ability to recognize letters generally still lowIn general, because the learning activities that are less attractive to children, is due to lack of teachers explore the game and also due to the limitations of instructional media.Recognize letters is very important for children as for preparation for the start of the next academic level. One of the reasons is lack of explore learning methods are used, making it less attractive for the children to follow the activity of learning to know the letters. Therefore researchers using game activity treasure chest contains a Letter to improve know letters the age groups 4-5 year in KoberAzkiya.As for the objectives of this study are: to find out initial conditions the ability to know the letter before and end the game used the treasure chest Contains the letters in KoberAzkiya, and to know determine the applicability of game treasure chest Contains the letters in KoberAzkiya. The method used is the class action Research (PTK), the implementation consists of three cycles, the cycle I and cycle II was given the two acts While cycle III was given a single action. Analysis and discussion of the results is poured by descriptive. Observations the ability to know the letter age groups 4-5 years of post cycle I once given action game through treasure chest Contains the letter proved to be increased, i.e. 37% on average, 36% of categories on category sufficient and 27% in the category of less. Observations on cycle II improved longer be 55% on average, 45% of the categories on the category is enough. Cycle III the increase to 73% in the good category and 45% in the category is sufficient. The development is considered sufficient when compared to prior givenaction game through treasure chest Contains letters. Recommendations for teachers expected to able to vary the thementhods and strategies of learning so that learning is monotonous for schools should be facilitated to support the teaching and learning process. The researcher expected to find an locate dansstrategi different menthonds improve the abilty to recognize letters for early childhood.